Effect of Instructional Videos on Postoperative Respiratory Function in Patients Undergoing Off-Pump Open Heart Surgery - Amirreza Salehmoghaddam; Amir Zoka; Seyedreza Mazlom; Shahram Amni (Mashhad University of Medical Sciences, 2016)
Background: Respiratory function in patients undergoing open heart surgery is disrupted after surgery.  Patient education on managing complications can reduce occurrence or severity of them. A variety of educational tools has been introduced, but there are controversies about the most appropriate tools. Aim: Determine the effect of instructional videos on respiratory function of the patients after off-pump open heart surgery. Method: This single-blind randomized clinical trial was conducted on 60 patients undergoing open heart surgery hospitalized at open heart surgery ward of Imam Reza (AS) hospital in Mashhad, Iran, in 2015. The patients were randomly allocated to intervention and control groups of 30 subjects. The instructional video during a 15-minute session was displayed in the intervention group and the control group educated by pamphlet and face-to-face training the day before the surgery. The respiratory function in both groups was assessed before intervention through spirometric variables including forced expiratory volume in 1 second (FEV1) and vital capacity (VC). After surgery, arterial oxygen saturation (SaO2) and PaO2/FiO2 Ratio (PF ratio) were measured 30 minutes after extubation, as well as the variables of FEV1, VC, SaO2 and PF ratio 24 hours after extubation. Data were analyzed by independent t-test, Mann-Whitney, Chi square, paired t-test, Wilcoxon and Friedman using SPSS version 11.5 software. Results: The means age of patients were 57.5±4.8 and 56.2±4.2 years in the intervention and the control groups, respectively. The difference of the PF ratio 24 hours after extubation compared to 30 minutes after extubation in the intervention group was significantly higher than the control group (P